The integrated stress response promotes macrophage inflammation and migration in autoimmune diabetes - Jiayi E. Wang; Charanya Muralidharan; Armando A. Puente; Titli Nargis; Jacob R. Enriquez; Ryan M. Anderson; Raghavendra G. Mirmira; Sarah A. Tersey (Cell Communication and Signaling)
Abstract Type 1 diabetes (T1D) is an autoimmune disease characterized by the destruction of insulin-producing pancreatic β-cells. Macrophages infiltrate islets early in T1D pathogenesis, preceding the influx of T- and B-lymphocytes. The integrated stress response (ISR), a cellular pathway activated during stress, coordinates adaptive changes in gene expression to maintain cell function and survival. To study the ISR in macrophages, bone-marrow-derived macrophages were treated with a pharmacological inhibitor of the ISR (ISRIB) and polarized to a proinflammatory M1-like state. We observed a reduction in the number of proinflammatory macrophages, as well as a decrease in iNOS mRNA and protein levels, following ISRIB treatment. RNA-sequencing revealed a reduction in pathways related to stress responses, including ER stress, reactive oxygen species (ROS) regulation, and autophagy, as well as migration pathway genes. ISRIB treatment led to decreased macrophage migration after stimulation in vitro and reduced migration of macrophages to the site of injury after tailfin injury in zebrafish in vivo. Interestingly, ISRIB mediated reduction of M1-like macrophages and reduction of migration was recapitulated by the inhibition of PKR but not PERK, both upstream ISR kinases, highlighting PKR as a key mediator of the ISR in macrophages. Pre-diabetic female non-obese diabetic (NOD) mice administered ISRIB demonstrated an overall reduction in the macrophage numbers in the pancreatic islets. Additionally, the insulitic area of pancreata from ISRIB treated NOD mice had increased PD-L1 levels. PD-L1 protein but not mRNA levels were increased in M1-like macrophages after ISR and PKR inhibition. Our findings identify the ISR, particularly via PKR, as a critical regulator of macrophage driven inflammation and migration in T1D. Our study offers new insights into ISR signaling in macrophages, demonstrating that the ISR may serve as a potential target for intervention in macrophages during early T1D pathogenesis.